2009
DOI: 10.1007/s10767-009-9060-1
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Trauma as a Potential Symbolic Boundary

Abstract: Using the case of the Holocaust as a cultural trauma in the Jewish-Israeli context, some insights are suggested as to the ways younger members of collectives view cultural trauma as a symbolic boundary. The findings obtained from three groups of students, each expressing their views on a different facet of the Holocaust as a symbolic boundary, suggest that the major contributing factor that turns cultural trauma into a symbolic boundary is the way in which members of the collective categorize the modes through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
(14 reference statements)
0
5
0
1
Order By: Relevance
“…This suggests that intended online commemoration of cultural trauma takes into consideration the exclusion of those considered disrespectful of the memory of the trauma. 16 As for messages, OWCs mainly discussed two aspects found to reflect the perceived influences of the Holocaust on Israeli society and culture as a cultural trauma, 12 namely the need for group solidarity and for keeping the memory of the Holocaust ever present in the face of attempts to erode it. In that respect, OWCs aim to convey the dominant cultural interpretations and perceptions by their cohort of the cultural trauma online.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that intended online commemoration of cultural trauma takes into consideration the exclusion of those considered disrespectful of the memory of the trauma. 16 As for messages, OWCs mainly discussed two aspects found to reflect the perceived influences of the Holocaust on Israeli society and culture as a cultural trauma, 12 namely the need for group solidarity and for keeping the memory of the Holocaust ever present in the face of attempts to erode it. In that respect, OWCs aim to convey the dominant cultural interpretations and perceptions by their cohort of the cultural trauma online.…”
Section: Discussionmentioning
confidence: 99%
“…Alevi identity is defined in contrast to Sunni Muslims (So ¨kefeld, 2008) and by a narrative about the collective trauma of Madımak. The contrast and trauma function as symbolic boundaries that create and sustain a sense of groupness and feelings of similarity among Alevis (Lazar & Litvak-Hirsch, 2009;Muro, 2009). The virtuous nature of the Alevi identity is contrasted with the oppressive and violent Sunni character.…”
Section: Discussionmentioning
confidence: 99%
“…Social identities depend on the kind of functional interdependence between the ingroup and specific outgroups. Furthermore, research has shown that victim beliefs and collective victimhood play an important role in sustaining and fueling conflicts between groups (e.g., Bar-Tal, Chernyak-Hai, Schori, & Gundar, 2009;Eyerman, 2004b;Lazar & Litvak-Hirsch, 2009;Muro, 2009 powerful symbols and effective instruments for creating a sense of victimhood. A sense of being a victim reminds group members of past violent acts by the rival and indicates that they could recur.…”
Section: The Social Identity Perspectivementioning
confidence: 99%
“…Such a micro perspective is also rather neglected in studies on cultural trauma that can work as a symbolic boundary (Lazar and Litvak-Hirsch, 2009). While scholarly work on collective memory and cultural trauma has been a quickly growing field in recent years, studying the (trans)formation of narratives on historical events (e.g., Alexander et al, 2004; Eyerman, 2002), relatively little attention has been paid to how cultural trauma resonates in the everyday life of social actors.…”
Section: Symbolic Boundaries and Cultural Traumamentioning
confidence: 99%